Workplace, human capital and ethnic determinants of sickness absence in Sweden, 1993 -2001 - Tommy Bengtsson; Kirk Scott (Institute for the Study of Labor (IZA), 2008)
This study charts the differences between the sickness absence of immigrants and Swedes during a period when a flourishing labour market in the beginning of the 1990s turned into a tense and problematic one. We consider not only human capital factors for various immigrant groups and natives, but also workplace conditions and macro level factors. Using register based information on 100,000 individuals for the period 1992-2001, we find large differences in sickness absence between natives and several immigrant groups and that these differences persist after controlling for human capital, workplace factors, and macro economic factors.
urn:nbn:de:101:1-2008091722
Keywords: J15; 330; Immigration; health; sickness benefits; labour market; integration; Erwerbsunfähigkeit; Fehlzeit; Migranten; Ethnische Gruppe; Humankapital; Arbeitsbedingungen; Schweden; Welt